Significantly enhanced activity of ZIF-67-supported nickel phosphate for electrocatalytic glucose oxidation. (1st May 2019) - Xiao, Lili; Zhao, Qing; Jia, Lin; Chen, Qi; Jiang, Jin; Yu, Qiyu
Abstract: Nickel-based nanoparticles have been widely used in detection of glucose due to its multiple oxidation states and high stability in alkaline environment. In this work, amorphous nickel phosphate was supported by Co-based zeolitic imidazolate framework (ZIF-67) through ion exchange to prepare Ni3 (PO4 )2 @ZIF-67 composites as the electrode material. In comparison to glassy carbon electrode (GCE), Ni3 (PO4 )2 /GCE and ZIF-67/GCE, the Ni3 (PO4 )2 @ZIF-67/GCE showed significantly enhanced performances in electrocatalytic oxidation of glucose. The great improvement on glucose oxidation current could be ascribed to the unique structure of Ni3 (PO4 )2 @ZIF-67, the mutual promotion between Ni(III)/Ni(II) and Co(IV)/Co(III) interfacial redox reactions and increased surface areas. Under optimum conditions, as-prepared Ni3 (PO4 )2 @ZIF-67/GCE showed an ultra-high sensitivity of 2783 μA mM −1  cm −2 with a wide linear ranged from 1.0 μM to 4.0 mM, and a low limit detection of 0.7 μM at a signal-to-noise ratio of 3. Moreover, Ni3 (PO4 )2 @ZIF-67/GCE were successfully applied to detect glucose of human serum with good recoveries (92–109%), which indicated that Ni3 (PO4 )2 @ZIF-67 can found application in the clinical detection. Graphical abstract: Image 1 Highlights: Ni3 (PO4 )2 @ZIF-67 with defective pores was facilely prepared through ion exchange. High surface area of 354 m 2  g −1 contributes to improve electrocatalytic properties. Open pores of Ni3 (PO4 )2 @ZIF-67 are conduce to unimpeded transfer for glucose. Ni3 (PO4 )2 @ZIF-67 has high sensitivity (2783 μA mM −1  cm −2 ) for detection of glucose. Ni3 (PO4 )2 @ZIF-67 is feasible to detect blood glucose for its good recoveries.